1991
DOI: 10.1103/physrevb.43.2866
|View full text |Cite
|
Sign up to set email alerts
|

Two observable features of the staggered-flux phase at nonzero doping

Abstract: We investigate whether the staggered-Aux phase (SFP) is realized in slightly doped phases of the Cu-0 high-T, superconductors. Using a mean-field solution of the t-J model, we calculate the size of circulating currents in the Cu02 planes. For realistic parameters we find nonzero currents when the doping 6 &0. 12. Taking into account structural details, we calculate the physical magnetic-field strength and the neutron-scattering cross section. The static field at the muon site varies between 0 and 100 G dependi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
123
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(134 citation statements)
references
References 39 publications
10
123
0
Order By: Relevance
“…4, 5 Chakravarty et al 6 have suggested that the pseudogap stems from a hidden order denoted by a d-density-wave (DDW) phase that competes with superconductivity and explains in a natural way the doping dependence of T C . This state is similar to circulating currents around the Cu-O bonds resulting from the staggered flux phase of the t-J model introduced by Hsu et al 7 These currents would produce a small magnetic field directed largely along the c-axis of the superconducting crystal and should be visible in a sufficiently accurate neutron scattering experiment. 8 Here we present data demonstrating the present capability to observe such a state and show that the best measurements suggest the possibility of such a state rather than showing a null result.…”
supporting
confidence: 62%
“…4, 5 Chakravarty et al 6 have suggested that the pseudogap stems from a hidden order denoted by a d-density-wave (DDW) phase that competes with superconductivity and explains in a natural way the doping dependence of T C . This state is similar to circulating currents around the Cu-O bonds resulting from the staggered flux phase of the t-J model introduced by Hsu et al 7 These currents would produce a small magnetic field directed largely along the c-axis of the superconducting crystal and should be visible in a sufficiently accurate neutron scattering experiment. 8 Here we present data demonstrating the present capability to observe such a state and show that the best measurements suggest the possibility of such a state rather than showing a null result.…”
supporting
confidence: 62%
“…This relation follows from the symmetry of the momentum sum and Equation 15. The structure factor in Equation 42 takes the same value at the two smallest scattering angles corresponding to the points Q 2 b = (π, 0, π) and Q 4 b = π in the reciprocal lattice:…”
Section: Neutron Scatteringmentioning
confidence: 95%
“…The muons in a µSR experiment might see a lowwer field if they sit at points of high symmetry or away from the plane. The orbital magnetic moments are likely to be dwarfed by local spin moments [3]. Incommensurate ordering may or may not break T ; if it does, the above analysis applies.…”
Section: Experimental Signaturesmentioning
confidence: 96%